Sterilization versus disinfection of the dental handpieces (pilot study) - Mohamed, Khadiga (Libyan Journal of Science &Technology, 2022)
Improperly following the cross-infection policy can transfer infection from infected patients to others. The Handpieces are the most important workhorse devices properly in all dental procedures. A retro-contamination may occur through their use of a septic environment. Unaware dentists could reuse a contaminated dental handpiece only after wiping with disinfectant. Objectives: To evaluate the infection control status of the wiped handpiece. Moreover, to increase the awareness of dentists toward this issue. Methods: Ten contaminated Handpieces were collected from the dental clinic. They swabbed from their external and internal surfaces and cultured in two types of growth culture media. Next, they were wiped (with InstruPlusForte Sol), swabbed and cultured again. In the last step, the handpieces were sterilized and swabbed for culturing in the same manner. The results: The wiped Handpieces showed that only three (30%) had no bacterial growth from their external surfaces, While 100% revealed the bacterial growth from their internal surfaces. No growth with sterilized Handpieces was demonstrated. Conclusion: Wiping the outside of the handpiece with disinfectant does not eliminate the potential cross-infection risk.